The Manufacture of Soda by the Ammonia Process - Oswald J. Heinrich (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
THE serious objections to the Leblanc soda process may be enumerated as follows : 1st. The total loss of sulphur employed, equal to about one-third of soda produced. Various processes have been proposed to regain this sulphur, but none have come into practical operation on a large scale. 2d. The great bulk of waste products, equal to nearly twice the amount of soda, which forms a serious annoyance about the works. 3d. The complicated series of operations necessary. 4th. The large amount of labor and fuel required. 5th. The production of noxious gases which necessitate extensive condensing arrangements. 6th. The large capital necessary for the erection and maintenance of the plant. These objections have long been recognized, and many attempts have been made during the last thirty or forty years, to discover and introduce a cheaper and more direct method for the manufacture of this important staple. The reaction between bicarbonate of ammonia and common salt, whereby bicarbonate of soda, insoluble in a solution of chloride of ammonium, is precipitated, has been closely studied for the last twenty-four years, on account of its simplicity and the purity of the product it affords. This ammonia-soda process is now so far developed, that while it is not .in position to entirely replace the Leblanc process, yet it can successfully compete with it where the conditions and localities are favorable. The advantages of the ammonia-soda process may be summed up as follows : 1st. It is independent of the essential agent in the Leblanc process, viz., sulphuric acid, and hence can be established in those localities where salt is abundant, and yet where sulphuric acid could not be made, or where it could not be transported profitably. 2d. The ammonia-soda process being a " wet" process, the evaporation of salt brines to obtain the solid salt required in the Leblanc process, is rendered unnecessary. 3d. The direct conversion of chloride of sodium into bicarbonate of soda, which can readily be converted into the maketable monocar-